Synthesis and Pharmacological Activity of a New Series of 1‐(1H‐Indol‐4‐yloxy)‐3‐(2‐(2‐methoxyphenoxy)ethylamino)propan‐2‐ol Analogs. Issue 3 (8th February 2016) - Bednarski, Marek; Otto, Monika; Dudek, Magdalena; Kołaczkowski, Marcin; Bucki, Adam; Siwek, Agata; Groszek, Grażyna; Maziarz, Elżbieta; Wilk, Piotr; Sapa, Jacek
Abstract : β‐Adrenergic receptor antagonists are important therapeutics for the treatment of cardiovascular disorders. In the group of β‐blockers, much attention is being paid to the third‐generation drugs that possess important ancillary properties besides inhibiting β‐adrenoceptors. Vasodilating activity of these drugs is produced through different mechanisms, such as nitric oxide (NO) release, β2 ‐agonistic action, α1 ‐blockade, antioxidant action, and Ca 2+ entry blockade. Here, a study on evaluation of the cardiovascular activity of five new compounds is presented. Compound3a is a methyl and four of the tested compounds (3b –e ) are dimethoxy derivatives of 1‐(1 H ‐indol‐4‐yloxy)‐3‐(2‐(2‐methoxyphenoxy)ethylamino)propan‐2‐ol. The obtained results confirmed that the methyl and dimethoxy derivatives of 1‐(1 H ‐indol‐4‐yloxy)‐3‐(2‐(2‐methoxyphenoxy)ethylamino)propan‐2‐ol and their enantiomers possess α1 ‐ and β1 ‐adrenolytic activities and that the antiarrhythmic and hypotensive effects of the tested compounds are related to their adrenolytic properties. Abstract : Five new derivatives of 1‐(1 H ‐indol‐4‐yloxy)‐3‐(2‐(2‐methoxyphenoxy)‐ethylamino)propan‐2‐ol (methyl and dimethoxy derivatives) are evaluated for their cardiovascular activities. All derivatives and their enantiomers possess α1 ‐ and β1 ‐adrenolytic activities. The antiarrhythmic and hypotensive effects of the tested compounds are related to their adrenolytic properties.